2013
DOI: 10.1021/bm301984w
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a Nitric Oxide-Releasing Nanofibrous Gelatin Matrix

Abstract: Nitric oxide (NO) plays an important role in cardiovascular homeostasis, immune responses, and wound repair. The pro-angiogenic and antimicrobial properties of NO has stimulated the development of NO-releasing materials for wound dressings. Gelatin, an abundant natural biodegradable polymer derived from collagen, is able to promote wound repair. S-Nitroso-N-acetylpenicillamine (SNAP) can release NO under physiological conditions and when exposed to light. The objective of this project was to fabricate a NO-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…To improve the NO payload and stability, achieve targeted NO delivery through multi-functionalization and elongate NO releasing lifetime, many different scaffolds have been used as NO-releasing or NO-generating vehicles. These include micelles, 138,190,191 microbubbles, 192 proteins, 193197 liposomes, 126,198 inorganic nanoparticles (such as silica, 70,199203 gold, 204,205 microparticles, 198,206 zeolites, 207,208 ), metal-organic frameworks (MOFs), 209212 dendrimers, 71,213,214 xerogels, 215217 electrospun fibers, 88,100,218 natural polymers (chitosan, 8587,219221 gelatin, 222 etc. ), and other organic polymers (polymethacrylate, 223 polyester, 224,225 polydimethylsiloxane (PDMS), 226 polysaccharides, 227,228 hydrogel, 178,179,229,230 PVA, 49,231,232 polyurethanes, 161,162,233,234 and PVC 154 ).…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the NO payload and stability, achieve targeted NO delivery through multi-functionalization and elongate NO releasing lifetime, many different scaffolds have been used as NO-releasing or NO-generating vehicles. These include micelles, 138,190,191 microbubbles, 192 proteins, 193197 liposomes, 126,198 inorganic nanoparticles (such as silica, 70,199203 gold, 204,205 microparticles, 198,206 zeolites, 207,208 ), metal-organic frameworks (MOFs), 209212 dendrimers, 71,213,214 xerogels, 215217 electrospun fibers, 88,100,218 natural polymers (chitosan, 8587,219221 gelatin, 222 etc. ), and other organic polymers (polymethacrylate, 223 polyester, 224,225 polydimethylsiloxane (PDMS), 226 polysaccharides, 227,228 hydrogel, 178,179,229,230 PVA, 49,231,232 polyurethanes, 161,162,233,234 and PVC 154 ).…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
“…Evidence suggested that 67 % of the photoinitiated NO was accounted for by the longer wavelength (590 nm) and 33 % by shorter wavelengths (centered around 340 nm). SNAP has also been covalently attached to PDMS, 226 gelatin 222 and a macrocycle (e.g., cyclam). 243 The ability to generate programmable sequences of NO flux from these light-sensitive materials can offer precise spatial and temporal control of the NO release and potentially provides a platform to systematically study, at a fundamental level, the in vivo physiological response to implanted devices.…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Various nano platforms have been proved successful in delivering NO. [14][15][16][17][18][19][20][21] Remarkably, these NO-releasing NPs exhibit a wide range of potential therapeutic activities, including antitumor effect. [22][23][24][25] In the present study, NO-releasing 4 S-nitroso silica NPs (SNO-SiNPs) were prepared from a single silane source using a surfactantfree and energy-efficient approach.…”
mentioning
confidence: 99%
“…8,[37][38][39][40] Here, titaniumand cell-adhesive gelatin was prepared by chemical modification with phosphate groups as a biological approach to enhance cell functions on titanium surfaces. We found that the gelation temperature was reduced by the modification and time-of-flight secondary ion mass spectrometry (ToF-SIMS) showed direct bonding between the phosphonated gelatin and the titanium surface.…”
mentioning
confidence: 99%